Comparing Burstable and On-Demand AWS EC2 Instances using NAS Parallel Benchmarks - Ferrari, Gian Carlo F.; Filho, Vanderlei; Castro, Márcio (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS); 2024: Anais da XXIV Escola Regional de Alto Desempenho da Região Sul, 2024)
Amazon Web Services (AWS) offers burstable instances, which have a baseline CPU performance with the ability to burst above the baseline as long as is required. In this paper, we evaluate the performance and monetary costs of NAS Parallel Benchmarks running on AWS burstable and standard virtual machines. Our results show that burstable instances can perform similarly with lower or similar monetary costs for some parallel applications.